Law enforcement in Malawi conservation: a monitoring system - Bell, R. (Pachyderm, 1984)
Outlines a monitoring system based on the systematic use of patrol reports produced by field staff. The system is intended to quantify patrolling effort, quantify the illegal activity encountered by patrols according to a set of standardized categories, and derive indices of the amount of illegal activity recorded per unit of patrolling effort. Patrol staff is trained to record data in a standard format. In the case of elephant there are 17 record points including the date of death, method of discovery, cause of death, presence or absence of tusks, age, etc. Data can be used to monitor preformance of patrol activity, to monitor changes in illegal activities, and to assess the impact of illegal activity on the mortality of key species and trade in their products. The value of this procedure as a management tool was evident in the case of elephant poaching in Kasungu NP. The few years prior to 1981 showed an upsurge in elephant poaching, but no enforcement was forthcoming, in 1982 the Park came under new and active leadership which included the monitoring system, a positive enforcement response was immediate.